Association of chlorhexidine and high fluoride dentifrice on Streptococcus mutans viability using an in vitro biofilm model - Santana, Guilherme Bandeira; Silva, Debora Lima; Ferreira, Josie Haydée Lima; Rolim, Fabiana Gouveia; Vale, Glauber Campos (Brazilian Dental Science, 2016)
Objective. This in vitro study investigated the effect of Fluoride (F), Chlorhexidine (CHX), and their association on the viability of Streptococcus mutans using a biofilm model. Materials and Methods. Biofilms were anaerobically grown on glass slides that were vertically suspended in 24-well plates for 5 days.  After 48 h of initial growth, biofilms were treated for the next 72 h, 2x/day with CHX at 0.12% and 2%, F as NaF at 0.08% and 0.4% and their association. Results. CHX treatment decreased the bacteria counts either alone or in association with both F concentrations, when compared with control group and the F treatments alone (p